The Effect of Sub-Acute Inhalation Exposure to Polyethylene and Polyvinyl Chloride Micro-Nano Plastics on the Superoxide Dismutase (SOD) Level and Malondialdehyde (MDA) Level in Rat Ovary - Sulistomo, Hikmawan Wahyu; Janasti, Laksmitha; Sari, Riana Trinovita; Kusworini, Kusworini; Ratnaningrum, Safrina Dewi; Kusuma, Ihda Dian; Nurdiana, Nurdiana (JURNAL INFO KESEHATAN, 2024)
Plastic is a synthetic or semi-synthetic organic polymer widely used in daily life and industrial production. Microplastics are widespread contaminants and can enter the human body by consuming foods containing microplastics, inhaling microplastics in the air, and making skin contact with microplastic particles in products. Microplastics can enter the ovaries as foreign bodies and can cause inflammation, oxidative stress, and even ovarian granulosa cell death. Polyethylene plastic shards generally have a higher ability to absorb environmental toxins than other types of plastic. Polyvinyl chloride (PVC) is one of the oldest thermoplastic polymers that is often used as water pipes. PVC has carcinogenic monomers and some harmful additives. This study aims to determine the effect of subacute exposure to micro-nanoplastics per inhalation on SOD and MDA levels in rat ovaries. The research method used is a true experimental design with a Randomize Post Test Only Group Design research design. This study used the ovarian organs of female white rats exposed to PVC and PE for 28 days. The number of samples used in this study amounted to 18 female rats. Subacute exposure to micro-nanoplastics per inhalation can lower SOD levels and significantly increase MDA levels in rat ovaries. This study is expected to provide knowledge and an overview for future research on the mechanism of toxicity of micro-nanoplastic exposure that has an impact on female infertility through free radicals in the ovaries.